1969
DOI: 10.1161/01.cir.39.5s1.i-91
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Intervention in Chronic Postinfarction Cardiac Failure

Abstract: Seven patients with severe, chronic postmyocardial infarction cardiac failure underwent open intracardiac operation following catheterization and quantitative biplane angiocardiographic studies. Four patients with mitral incompetence had valve replacements; three had dilated mitral rings and did not survive the immediate postoperative period. In contrast, the single surviving patient had papillary muscle dysfunction evident at surgery and had less severe myocardial impairment as indicated preoperatively by a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1970
1970
1980
1980

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Glass et al (3) found that the cardiac output as well as the systemic blood pressure improved significantly following resection of experimentally induced infarction in animals. In man the hemodynamic studies published by Harman et al (5) and Lajos et aI. (10) showed that, after resection of old infarction, the majority of the patients improved in end-diastolic volume and pressure and in cardiac output.…”
Section: Operatlve Techniquementioning
confidence: 98%
“…Glass et al (3) found that the cardiac output as well as the systemic blood pressure improved significantly following resection of experimentally induced infarction in animals. In man the hemodynamic studies published by Harman et al (5) and Lajos et aI. (10) showed that, after resection of old infarction, the majority of the patients improved in end-diastolic volume and pressure and in cardiac output.…”
Section: Operatlve Techniquementioning
confidence: 98%